Infantile Scurvy: Two Case Reports - Leila Ghedira Besbes; Samir Haddad; Chebil Ben Meriem; Mondher Golli; Mohamed-fadhel Najjar; Mohamed-Néji Guediche (International Journal of Pediatrics)
Background. Ascorbic acid (vitamin C) is necessary for the formation of collagen, reducing free radicals, and aiding in iron absorption. SCURVY, a disease of dietary ascorbic acid deficiency, is uncommon today. It still exists in high risk groups including economically disadvantaged populations with poor nutrition. The incidence of SCURVY in the pediatric population is very low. Cases Report. Here we report two cases of SCURVY revealed by subperiosteal hematoma in children with cerebral palsy and developmental delay. Conclusion. SCURVY is extremely rare in children. Musculoskeletal manifestations are prominent in pediatric SCURVY. Multiple subperiosteal hematomas are an important indicator for diagnosis.